Possible Involvement of Tissue Plasminogen Activator/Brain-Derived Neurotrophic Factor Pathway in Anti-Depressant Effects of Electroacupuncture in Chronic Unpredictable Mild Stress-Induced Depression in Rats - Luo, Tong; Tian, Huiling; Song, Hongtao; Zhao, Jun; Liya, Ai; Fang, Yumin; Mou, Junhui; Li, Zhigang; Chaoketu, Saiyin (Frontiers in Psychiatry, 2020)
Abstract Objective: Using a rat model of chronic unpredictable mild stress (CUMS), to investigate the effects of electroacupuncture (EA) on the tissue plasminogen activator (tPA)/brain-derived neurotrophic factor (BDNF) pathway. Methods: Sixty male Sprague-Dawley rats were randomly divided into four groups: normal, model, fluoxetine (fluox), or EA. Experimental groups were subjected to 28 d of CUMS modeling. One hour after CUMS, the fluox and EA groups were treated with ﬂuox and a 20 min EA intervention, respectively. Depressive-like behaviors were assessed by open field and sucrose preference tests. After the rats were sacrificed, brains were dissected and processed using hematoxylin and eosin (HE) staining to observe changes in the morphology and quantity of neurons in the hippocampal cornu ammonis 3 area. Western blot and real-time polymerase chain reaction (PCR) demonstrated the effects of EA on the tPA/BDNF pathway-related molecules in the hippocampi and raphe nuclei. Results: Compared to the model group, the number of horizontal and vertical movements and the percentage of sucrose consumption in the EA groups were significantly increased (P < 0.01). Compared to the model group, HE staining showed that the hippocampal neurons in the EA and fluox groups were arranged neatly, with rich layers and complete cell structures. The Western blot and real-time PCR showed that the levels of tPA, BDNF, tropomyosin receptor kinase B, and BDNF micro RNA (mRNA) in the hippocampi of the EA group were higher than in the model group (P < 0.01, P < 0.01, P < 0.05, P < 0.01, respectively). The content of p75NTR, proBDNF, and tPA mRNA in the hippocampi of the EA group displayed no significant differences compared to the model group. The tPA mRNA content in the raphe nuclei of the EA group was higher than in the model group (P < 0.01), and the BDNF content in the raphe nuclei was lower than in the model group (P < 0.05). There were no significant differences in tPA and BDNF mRNA between the EA and model groups. Conclusion: EA may reverse depressive-like behaviors in CUMS, which may be related to the tPA/BDNF pathway in the hippocampus.